Problema del fundamento de las aproximaciones morales a la propuesta ética de Arthur Schopenahuer - Castillo Rafael, Carlos (2016)
It is always pertinent, in view of the presentation and clarity in the development of a topic, to delimit not only the scope of what is going to be studied but also to specify what is the problem that somehow will try to solve as Part of the research topic of the referral. This is more true when the topic is shown from the beginning in the form of a problem, so specifying this issue is both defining the scope of our analysis. Now, for the purpose of stating how the problem is understood as regards the foundation of morality, we will point out, previously (and as part, precisely, of the question in general) why this is a problem.